Um estudo da aliança estratégica da CONFEPAR, sob a ótica das preferências dos produtores de leite vinculados - Schwans, Scheila Aparecida Kulka (2011)
The economic transformations that happened in the 1990 s have conditioned the formation of strategic alliances among singular milk cooperatives in the state of Paraná. For this study, the research environment was the conglomerate of singular cooperatives bound to the Cooperativa Central Agroindustrial Ltda CONFEPAR, cooperatives which form one of four dairy products alliances. After a decade of existence of this alliance, this study tried to know the aspirations of milk producers bound to it, that is, subsidies were sought for a reevaluation of the strategies adopted by this alliance. The study deals with the following theme: A study of the strategic alliance CONFEPAR, from the viewpoint of bound to the alliance milk producers preferences , with its main goal as to verify the preferences of milk producers bound to the singular cooperatives that form this strategic alliance. In order to guarantee growth and to obtain competitive advantages for the group and the maintenance of these producers, it is necessary to continuously reevaluate business strategies. From this viewpoint, the value of such a study is stressed, because knowing these preferences may represent an important differential to structure new strategies, and to satisfy the involved producer s individual needs. To obtain the goals proposed by this study, a research using Declared Preference technique was conducted, a technique which made possible, after statistical treatment through the software LMPC, to evidence which are the most statistically relevant preferences from the bound to the alliance milk producers viewpoint.